PENGGUNAAN METODE ELECTRE DALAM PEMILIHAN PENYUPLAI BAHAN MATERIAL PROYEK DRAINASE - Ainul Riza Harahap; Boby Maulana; Ehrlich F.T. Butarbutar; Eko Widodo; Muhammad Andika (semanTIK, 2018)
This study was conducted to test and prove that the Elimination Et Choix Traduisant La Reality (Electre) method can be used to select drainage project material suppliers from some alternatives with predetermined criteria. The criteria used are 3, including Price, Quality, and Distance. Sample data used are 5 alternatives with different weighting values for each of the criteria. Suppliers are people who supply. The application of supplier selection is still be dominated by price factors and input from experienced staff. The data used is obtained from the UPT archive. Spatial Planning and Settlement of Pematangsiantar in 2016, where the final results can be recommended to agencies in the selection of suppliers of drainage project materials. The method used is the Elimination Et Choix Traduisant La Reality (Electre) method. From this Decision Support System (DSS), the final results which are chosen as suppliers of drainage project material are obtained.Keywords— Election, Material Suppliers, Drainage Projects, DSS, ElectreDOI : 10.5281/zenodo.2528127